2014
DOI: 10.1039/c4dt01534g
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the oxidation states of Zr and Co in a highly reactive heterobimetallic Zr/Co complex using X-ray absorption spectroscopy (XANES)

Abstract: The reduced heterobimetallic complex (THF)Zr(MesNP(i)Pr2)3CoN2 (1) has been examined along with a series of structurally similar reference compounds using X-ray absorption near edge structure (XANES) spectroscopy. Complex 1 has been shown to be highly reactive, often via one-electron pathways that might be expected for a d(1) Zr(III) complex. However, the presence of two strongly interacting metals in complex 1 renders the assignment of oxidation states ambiguous. Both Zr and Co K-edge XANES spectra reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 35 publications
(43 reference statements)
10
47
0
Order By: Relevance
“…Although limited experimental techniques are capable of probing metal–metal dative interactions, X-ray Absorption Near-Edge Spectroscopy (XANES) 71 has begun to find an important use in this regard. 30 , 34 Importantly, its utility lies in its ability to decipher the spectroscopic oxidation states of the metals involved in a given bonding interaction. In order to assess the degree of charge transfer inherent in the formation of a reverse-dative σ-interaction to Tl( i ), Pd K -edge XANES was carried out on the palladium–thallium adduct [TlPd(CNAr Dipp2 ) 2 ]OTf ( 2 , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although limited experimental techniques are capable of probing metal–metal dative interactions, X-ray Absorption Near-Edge Spectroscopy (XANES) 71 has begun to find an important use in this regard. 30 , 34 Importantly, its utility lies in its ability to decipher the spectroscopic oxidation states of the metals involved in a given bonding interaction. In order to assess the degree of charge transfer inherent in the formation of a reverse-dative σ-interaction to Tl( i ), Pd K -edge XANES was carried out on the palladium–thallium adduct [TlPd(CNAr Dipp2 ) 2 ]OTf ( 2 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 46 , 47 Similar ambiguities in the electronic structures of MOLPs exist, although considerably less effort has been put toward uncovering satisfactory electronic descriptors for such compounds. 39 Despite the fact that X-ray Absorption Near-Edge Spectroscopy (XANES) holds promise in this regard, 30 , 34 its thus-far limited use in this capacity has not yet led to the development of general principles for properly describing the electronic structures of complexes containing metal–metal dative interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in natural charge between the two metal atoms is far smaller for complex 3 (1.04) than for the previously described Zr/Co complex (THF)Zr(MesNP i Pr 2 ) 3 CoN 2 (2.61). 39 …”
Section: Resultsmentioning
confidence: 99%
“…A recent study using X-ray absorption near edge structure (XANES) spectroscopy showed that the effective oxidation states in the similar complex (THF)Zr(MesNP i Pr 2 ) 3 CoN 2 are Zr IV /Co –I . 39 However, given the polar covalent nature of the metal–metal σ bond, a non-zwitterionic Ti III /Co 0 description may be favored in the case of 3 and further spectroscopic study will be required to determine the effective oxidation states in this molecule.…”
Section: Resultsmentioning
confidence: 99%
“…I 2 , RX, CO 2 ) [11,12], and four-electron redox processes (RN 3 ) [13]. The versatile multielectron redox chemistry of (THF)Zr(MesNP i Pr 2 ) 3 CoN 2 is particularly remarkable given that the oxidation states of the two metals were found to be Zr IV and Co -I using XANES (X-ray Absorption Near Edge Structure) spectroscopy [14], so Co is serving as the sole source of electrons in all of the aforementioned multielectron redox processes. While exploring the reactivity and catalytic applications of (THF)Zr(MesNP i Pr 2 ) 3 CoN 2 , we found this complex is an effective catalyst for the hydrosilylation of ketones [15].…”
Section: Introductionmentioning
confidence: 99%